Targeting Non-Coding RNAs in Plants with the CRISPR-Cas Technology is a Challenge yet Worth Accepting - Basak, Jolly; Nithin, Chandran (Frontiers in Plant Science, 2015)
Non-coding RNAs (ncRNAs) have emerged as versatile master regulator of biological functions in recent years. MicroRNAs (miRNAs) are small endogenous ncRNAs of 18–24 nucleotides in length that originates from long self-complementary precursors. Besides their direct involvement in developmental processes, plant miRNAs play key roles in gene regulatory networks and varied biological processes. Alternatively, long ncRNAs (lncRNAs) are a large and diverse class of transcribed ncRNAs whose length exceed that of 200 nucleotides. Plant lncRNAs are transcribed by different RNA polymerases, showing diverse structural features. Plant lncRNAs also are important regulators of gene expression in diverse biological processes. There has been a breakthrough in the technology of genome editing, the CRISPR-Cas9 (clustered regulatory interspaced short palindromic repeats/CRISPR-associated protein 9) technology, in the last decade. CRISPR loci are transcribed into ncRNA and eventually form a functional complex with Cas9 and further guide the complex to cleave complementary invading DNA. The CRISPR-Cas technology has been successfully applied in model plants such as Arabidopsis and tobacco and important crops like wheat, maize, and rice. However, all these studies are focused on protein coding genes. Information about targeting non-coding genes is scarce. Hitherto, the CRISPR-Cas technology has been exclusively used in vertebrate systems to engineer miRNA/lncRNAs, but it is still relatively unexplored in plants. While briefing miRNAs, lncRNAs and applications of the CRISPR-Cas technology in human and animals, this review essentially elaborates several strategies to overcome the challenges of applying the CRISPR-Cas technology in editing ncRNAs in plants and the future perspective of this field.